TAX PLANNING - Kustiawan, Memen; solikin, ikin (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
Tax planning is the way to formulate a structure  concerning the consequency of tax  potential,  mainly focusing on the control of every transaction with tax consequence. The objective is  to assure  that the control over the transaction can make the tax to be transfered to government more efficient. However, the tax planning cannot be formed without  a deep survey  on the  problem to be structured in accordance with the tax law and procedures, after a consideration to other non-tax factors  including the strengths and weaknesses of the system. To sum up, an effective tax planning depends mostly on the awareness and involvement of decision makers to the  tax impact attached to any activities of the corporate, and not on the expertise of tax profesionnals.